The Use of the SERVQUAL Tool to Measure the Quality of Service in a Gym in the city of Abaetetuba-PA (Research, Society and Development, 2022)
The present work aims to measure the quality of the service provided in a gym located in the city of Abaetetuba. Therefore, the SERVQUAL model was used in order to assess the expectation and reality about the services provided. The SERVQUAL application was carried out online and through instant messaging applications, which generated the interviewees' satisfaction gaps. The survey was carried out with 60 customers and with the help of Excel software it was possible to obtain the individual gaps for each dimension, which showed a greater discrepancy in question 10, which concerns the willingness to help customers, which is part of the empathy, dimension that presented a negative gap with value (-0.57). After weighing the collected data and diagnosing the points of customer dissatisfaction, an improvement proposal was made with the help of the PDCA tool to improve the satisfaction of shoppers.